Numerical Investigation Of Reinforcement Ratio Effects on the Flexural Performance of High-Calcium Fly Ash Geopolymer Concrete Beams - Muhammad Rifky Trisnawardhana; Bambang Piscesa; Indra Komara (Journal of Applied Sciences, Management and Engineering Technology, 2026)
This study investigates the influence of the longitudinal reinforcement ratio on the flexural behavior of high-calcium fly ash geopolymer concrete (GPC) beams using three-dimensional nonlinear finite element analysis (3D NLFEA). Beams with identical geometry and shear reinforcement were modeled, with reinforcement ratios varied from under-reinforced to over-reinforced conditions. Material properties were based on validated experimental data. Results show that increasing reinforcement enhances flexural strength but significantly reduces ductility and energy absorption. Under-reinforced beams exhibited ductile, tension-controlled failure governed by steel yielding, while over-reinforced beams failed abruptly due to concrete crushing. The transition from ductile to brittle behavior occurs at significantly lower reinforcement ratios in GPC (around ρ = 0.0157) compared to ordinary Portland cement concrete. Based on ductility ratio, energy absorption, and toughness index i10, a maximum reinforcement ratio of ρ ≤ 0.010 is recommended for ductile design of high-calcium fly ash GPC beams.